2002
DOI: 10.1007/s00439-002-0719-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the WFS1 gene that cause low-frequency sensorineural hearing loss are small non-inactivating mutations

Abstract: Hereditary hearing impairment is an extremely heterogeneous trait, with more than 70 identified loci. Only two of these loci are associated with an auditory phenotype that predominantly affects the low frequencies (DFNA1 and DFNA6/14). In this study, we have completed mutation screening of the WFS1 gene in eight autosomal dominant families and twelve sporadic cases in which affected persons have low-frequency sensorineural hearing impairment (LFSNHI). Mutations in this gene are known to be responsible for Wolf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 18 publications
2
56
0
1
Order By: Relevance
“…155 Some of these mutations were subsequently found to be a common cause of inherited isolated lowfrequency hearing loss. 156 In one report, the locus on chromosome 4p16 was proposed as a predisposing factor for the formation of multiple mtDNA deletions. 157 DIDMOAD patients were also found to concentrate on two major mtDNA haplotypes that are also overrepresented among LHON patients.…”
Section: Other Monosymptomatic Hereditary Optic Neuropathiesmentioning
confidence: 99%
“…155 Some of these mutations were subsequently found to be a common cause of inherited isolated lowfrequency hearing loss. 156 In one report, the locus on chromosome 4p16 was proposed as a predisposing factor for the formation of multiple mtDNA deletions. 157 DIDMOAD patients were also found to concentrate on two major mtDNA haplotypes that are also overrepresented among LHON patients.…”
Section: Other Monosymptomatic Hereditary Optic Neuropathiesmentioning
confidence: 99%
“…They differ in their associated symptoms and inheritance mode, and although their most common clinical symptom is hearing loss, it is of different types. While DNFA6/14/38 is characterized by low frequency sensorineural hearing loss (LFSNHL), in contrast, Wolfram syndrome is associated with various hearing severities ranging from normal to profound hearing loss that is dissimilar to LFSNHL (Pennings et al 2002). To confirm whether within non-syndromic hearing loss patients WFS1 mutations are found restrictively in patients with LFSNHL and to summarize the mutation spectrum of WFS1 found in Japanese, we screened 206 Japanese autosomal dominant and 64 autosomal recessive (sporadic) non-syndromic hearing loss probands with various severities of hearing loss.…”
mentioning
confidence: 99%
“…Research suggested that most heterozygous WFS1 mutations are likely small non-inactivating mutations [74,77]. Interestingly, nine out of ten LFSNHI-associated WFS1 mutations affect the C-terminal protein domain of WFS1 [77].…”
Section: Wfs1 and Er Stressmentioning
confidence: 99%